SEX IN ANTIQUITY. EXPLORING GENDER AND SEXUALITY IN THE ANCIENT WORLD. - Razvan Bogdan Gaspar (Journal of Ancient History and Archaeology, 2015)
Sex in Antiquity. Exploring Gender and Sexuality in the Ancient World. Edited by Mark Masterson, Nancy Sorkin Rabinowitz and James Robson. Routledge: London and New York 2015. 567 pp. ISBN 978-0-415-51941-0 (hbk) and ISBN 978-1-315-74791-0 (ebk)